Study on Preparation Technology and Safety Evaluation of Hataagqi-19 Hydrogel Patch - Aruhan; Dorjsuren, Byambasuren; Song, Xiaoling; Chimedtseren, Chimedragchaa; Li, Minhui; Damba, Tsend-Ayush (Central Asian Journal of Medical Sciences, 2021)
Objectives: The study objective of the present study was to screen the dosage of matrix material and clarify the safety evaluation of Hataagqi-19 hydrogel patch. Methods: Single factor and orthogonal experiments were used to screen, and the best matrix ratio was screened out with peel strength, peel ability, viscosity, spread ability, uniformity, as evaluation indicators. Long term toxicity test was carried out in SD rats in order to test general conditions such as: body weight, food intake, electrocardiogram, blood, urine, and biochemical indicators, organ coefficients and histopathological changes. Moreover, skin allergic reaction tests were done to observe the allergic responce. Results: The ratio of the gel patch matrix is NP-700: aluminum glycolate: glycerol: carbomer = 6: 0.35: 35: 0.40; the ratio of azone and propylene glycol is 1: 1, and the total penetration enhancer dosage is 5%. Hataagqi-19 preparation had no obvious long-term toxicity or skin allergies. Conclusions: The Hataagqi-19 hydrogel patch prepared with the best ratio and transdermal agent showed good performance and safety. Furthermore, we did not observed toxic side effects, and the preparation process is feasible and reliable.